Appropriating Just Peacemaking Theory for Sustainable Peace in Papua: An Ethical Framework for Conflict Resolution - Mamahit, Ferry Y.; Mawikere, Christian Joel; Muetterties, Zachary T. (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2026)
The Papua conflict, with its deep roots in contested history, human rights violations, and economic marginalization, demands responses that are both ethically serious and practically grounded. This study asks whether Glen Stassen’s Just Peacemaking Theory can be applied to that context. Through qualitative conceptual analysis, it identifies practices within the theory most capable of translation to Papuan conditions—nonviolent direct action, human rights advocacy, sustainable development, grassroots peacebuilding—and works them into strategic orientations: empowering indigenous advocacy, insisting on inclusive development, strengthening local peace networks. For practical theology, the contribution is straightforward: it demonstrates how a normative ethical framework can be brought into genuine conversation with a live conflict, not as an abstract principle but as an adaptable resource. For Papuan churches, it offers a way of naming what they already do and a vocabulary for taking it further.